"To Tell It as We Know It": Black Women's History and the Archive of Brexit Britain. Issue 2 (1st June 2021) - Perry, Kennetta Hammond
Abstract: This article takes Beverley Bryan, Stella Dadzie, and Suzanne Scafe's The Heart of the Race (1985 ) as an invitation to consider the conditions that routinely mark formulations of Brexit Britain as they operated in the lives of Black women in Britain during the early 1980s. It explores how the text engages Black women's lives as an index of how the welfare state was both structured and experienced in such a way that demarcated racialized internal borders of Britishness, citizenship, and belonging. It also argues for the importance of embedding Black women's narratives into histories of Brexit's unfolding.